Evaluation of left ventricular myocardial stratified strain in patients with Kawasaki disease using two-dimensional speckle tracking imaging - Hu, Jinling; Zheng, Qiaojin; Ren, Weidong (Frontiers in Cardiovascular Medicine, 2022)
Kawasaki disease (KD) is an acute autoimmune self-limited disease of unknown etiology. We aimed to evaluate the left ventricular myocardial stratified strains in children with KD in different stages using two-dimensional speckle tracking imaging, and to find the index that can early predict myocardial function injury in children with KD. A total of 73 children with KD were divided into acute, convalescent, and chronic stages according to the disease course. Further, 64 normal children were selected as the control group. The longitudinal and circumferential strain peaks of each myocardium were recorded, and the left ventricular global longitudinal strain (LVGLS), global circumferential strain (LVGCS), and transmural gradient between endocardium and epicardium (GLS, GCS) were calculated. Compared with the control group, LVGLS, GLS-Endo, GLS-Mid, GLS-Epi, and GLS decreased in acute KD; LVGLS, GLS-Endo, GLS-Mid, GLS-Epi, GLS, LVGCS, GCS-Mid, and GCS-Epi decreased in the convalescent stage; and only GLS-Endo was lower in children with chronic KD (P < 0.05). ROC curve was used to calculate the stratified strain parameters so as to predict left ventricular systolic function in children with acute KD; the area under the LVGLS curve was the largest (AUC = 0.953, P < 0.001). When the cutoff value of LVGLS was -19.89%, the sensitivity and specificity were 95.8% and 83.2%, respectively. Conclusions: The systolic function of the whole layer of the myocardium decreased to varying degrees in children with KD. With the extension of the disease course, the myocardial function gradually recovered, but the subendocardial myocardium was still damaged. LVGLS could identify the abnormity of left ventricular contractility in patients with KD at the acute stage. Thus, it has the promising prospect of clinical diagnosis.